Student’s Perception of Service Quality in Education: A Study from Student responses of leading Malaysian Private Colleeges in the Klang Valley - Toh, Liu Hao (2011)
In Malaysia, there are more than 27% of local students who enroll in private colleges to further their studies every year. Currently, Malaysia government becomes less compromising with private institutions, especially in their in their service quality even the private institutions have already realize their weaknesses early. Hence, the researcher is performing a research is performing a research on the current students about the service quality providing by their institutions. In this study, questionnaires are used for data collection, questionnaires are distributed to students who studying at four institutions in Klang Valley. Then, the data anaylsis is performed using Pearson correlation, descriptive and Kendall tau-b. The result from the research showed a positive relationship between SERVQUAL dimensions and the five dimensions (Tangibility, Assurance, Reliability, Responsiveness and Empathy) in relation with student satisfaction. Among those dimensions, assurance dimension is higher than responsiveness, empathy, reliability and tangibility. Finally, conclusion, recommendations and personal reflections are provided based on the finding.